EFFECTIVE INTEREST RATE COMPARATION OF HONDA AND YAMAHA MOTORCYCLE CREDIT - Setio, Steve; Manalu, Sahala; Octavianus, Rony Joyo Negoro (Jurnal Aplikasi Manajemen, 2017)
This research was conducted to analyze the comparisons between credit's effective interest rate on Honda and Yamaha motorcycles based on the level of down payment and credit tenures during 2016. The sampling technique used was purposive sampling method. Data analysis techniques used was comparative analysis proposed by Nazir (2005) in Hamdi and Bachruddin (2014) which explain that the purpose of the comparative analysis investigates the relationship between one variable to another variable in order to find a comparison between two or more variables in a research. The results showed that the value average of the effective interest rate on Honda motorcycle was lower than Yamaha motorcycle. Based on the level of down payment and credit tenures; the lowest average of effective interest rate was at a level of 17,5 % from motorcycle the on the road price with credit tenures for 36 months.